Exploration of the Experiences of Lesotho Sleep in Domestic Workers in a Semi-Urban Settlement in Mthatha, Eastern Cape, South Africa - Ngcobo, Silindile; Magadla-Mateyise, Afika Fikiswa (Research in Social Sciences and Technology- OpenED Network, 2025)
This study, conducted through a combination of interviews, surveys, and direct observations, examines the exploitation of sleep-in domestic workers from Lesotho who work in South African households. Based on data collected from 15 participants, the research brings to light the difficult living conditions these workers face, including a lack of privacy and inadequate working environments. The study identifies several key issues, such as the absence of written contracts, leaving workers susceptible to exploitation, unpaid overtime, and widespread non-compliance with minimum wage laws. The research shows that domestic workers encounter major obstacles in getting necessary healthcare and support services, which worsens their already unstable situation. The study also emphasizes the lack of chances for training and skills improvement, which hampers the workers' ability to enhance their lives and find better job opportunities. Many of these domestic workers are the main providers for their families and single parents, making the importance of fair pay and good working conditions even more crucial. The study highlights the significance of fair pay and good working conditions, stressing the urgent need for these rights and immediate policy interventions to be upheld. The research aims to bring attention to the systemic exploitation faced by this vulnerable group and advocate for essential reforms to protect their rights and improve their living and working conditions. Overall, the study emphasizes the pressing need for policy interventions and support mechanisms to empower domestic workers and enhance their quality of life in South Africa.